Simbol Identitas Penggunaan Ayat Al-Qur'an dalam Film Indonesia: Kajian Semiotika Film Tenggelamnya Kapal Van Der Wijck dan Makmum - Alfathah, Suryana; Maulana, Rizqi Akbar (Jurnal Penelitian Ilmu Ushuluddin, 2023)
The purpose of this study is to identify the signs shown in the film Tenggelamnya Kapal Van Der Wijck and the film Makmum where the focus of this research is on the use of verses from the Qur'an throughout the film. This research is qualitative in nature with a literature study using Charles Sanders Pierce's semiotic approach. The conclusion of this study is that film can be a medium of Islamic da'wah that contains Islamic messages. The Islamic identity contained in the two films includes cultural aspects, characters, clothing, and rituals performed. The use of verses from the Qur'an in the film Tenggelamnya Kapal Van Der Wijck shows a message to study knowledge, social equality, serve parents, and believe in the power of Allah SWT. Meanwhile, in the film Makmum shows the attitude of human servitude for their weaknesses, asking for protection from Allah SWT, as well as signs of healing diseases through reciting verses from the Al-Quran.